2022
DOI: 10.1186/s12886-022-02399-7
|View full text |Cite
|
Sign up to set email alerts
|

Altered retinal nerve fiber layer thickness in children with allergic conjunctivitis: the Nanjing eye study

Abstract: Background So far, few data are available on the relationship between allergic conjunctivitis (AC) and ocular fundus. Whether retinal parameters change in patients with AC remains unknown. In this study, we investigated the influence of AC on retinal thickness and vessel density among 7-years-old school-age children. Methods This large population-based study is part of the Nanjing Eye Study (NES). Comprehensive examinations including anthropometric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Chen D et al reported a thinner retinal nerve ber layer (RNFL) in patients with allergic conjunctivitis (AC) [30]. The same study showed no signi cant difference in macular thickness measurements among AC patients compared to the control group.…”
Section: Discussionmentioning
confidence: 91%
“…Chen D et al reported a thinner retinal nerve ber layer (RNFL) in patients with allergic conjunctivitis (AC) [30]. The same study showed no signi cant difference in macular thickness measurements among AC patients compared to the control group.…”
Section: Discussionmentioning
confidence: 91%
“…Chen D et al reported a thinner retinal nerve fiber layer (RNFL) in patients with allergic conjunctivitis (AC) (30). The same study showed no significant difference in macular thickness measurements among AC patients compared to the control group.…”
Section: Discussionmentioning
confidence: 92%
“…The direct effect of topical corticosteroids and the RNFL thickness needs more research and until strong evidence suggests that topical corticosteroids affect the RNFL, we do not consider short-term use of uoromethalone 0.1% as a major confounding factor. The association between the retinal nerve bre layer and allergic conjunctivitis also requires further research as a single study reported a slightly thinner RNFL in Chinese children with allergic conjunctivitis (42). We did not consider the in uence of other optic nerve head parameters on the RNFL thickness.…”
Section: Strengths and Limitationsmentioning
confidence: 94%